Cryptocurrency and Digital Asset Regulation: A Comparative Analysis of Economic and Business Law in Indonesia and India - Dewi, Kadek Novita; Kurniawan, I Gede Agus (Faculty of Law, Universitas Pekalongan, 2025)
The rapid growth of cryptocurrencies and digital assets has created significant challenges for governments in regulating economic and business activities. Both Indonesia and India face similar issues concerning legal certainty, investor protection, and financial stability, yet they have adopted different regulatory approaches. This research aims to analyze and compare the regulatory frameworks governing cryptocurrencies and digital assets in Indonesia and India, using a comparative legal method that examines legislation, regulatory guidelines, and policies in both countries, supported by doctrinal interpretation and secondary literature. The findings reveal that Indonesia officially prohibits the use of cryptocurrencies as a means of payment but allows them to be traded as commodities under the supervision of the Commodity Futures Trading Regulatory Agency (Bappebti). In contrast, India has demonstrated a dynamic regulatory stance—initially imposing restrictions on cryptocurrency activities, later introducing a taxation framework, and currently considering the implementation of a central bank digital currency (CBDC). Despite these differences, both jurisdictions share the same fundamental objectives: to safeguard the financial system, prevent money laundering, and protect consumers. Indonesia’s approach emphasizes strict market controls and legal certainty through prohibitions on payment functions, while India’s model reflects regulatory fluidity and growing fiscal integration. This comparative analysis underscores the evolving nature of cryptocurrency governance in developing economies and highlights the need for balanced frameworks that promote innovation while maintaining financial stability and legal coherence.